Lymphoepithelial Pancreatic Cyst: An Atypical Benign Pancreatic Mass Presenting with a ’Cheerios-Like’ Appearance - Matrone, Alessia; Russo, Maria; Mollica, Carmine; Lombardi, Domenico; Lombardi, Guido; Maurea, Simone; Imbriaco, Massimo (JOP. Journal of the Pancreas, 2010)
Context Lymphoepithelial cyst of the pancreas is a rare benign lesion which often presents as an incidental radiological finding, but may cause symptoms, such as abdominal pain and nausea. It can occur at any location in the pancreas. The differential diagnosis includes primary splenic cysts, pseudocysts, mucinous cystic neoplasms of the pancreas, left adrenal cysts, duplication cysts and retroperitoneal cysts. Some of these diagnoses can be excluded by MRI; however, for the final diagnosis, fine needle aspiration or surgical resection may be necessary. Case report We report a rare case of a pancreatic lymphoepithelial cyst in an asymptomatic 63-year-old man, discovered in a clinical follow-up for colon cancer. In particular, we describe the unique "cheerios-like" appearance of the lesion which has never before been reported. Conclusion This particular finding could help in the differential diagnosis of this benign lesion from other pancreatic masses. Image: T2-weighted axial MR image showing a complex mass consisting of multiple sub-centimeter nodules, with a "cheerios-like" appearance.